2017
DOI: 10.1089/neu.2015.4381
|View full text |Cite
|
Sign up to set email alerts
|

Patients “At Risk” of Suffering from Persistent Complaints after Mild Traumatic Brain Injury: The Role of Coping, Mood Disorders, and Post-Traumatic Stress

Abstract: Although most patients recover fully following mild traumatic brain injury (mTBI), a minority (15-25%) of all patients develop persistent post-traumatic complaints (PTC) that interfere with the resumption of previous activities. An early identification of patients who are at risk for PTC is currently performed by measuring the number of complaints in the acute phase. However, only part of this group will actually develop persisting complaints, stressing the need for studies on additional risk factors. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 41 publications
2
40
1
1
Order By: Relevance
“…The population with negative coping style showed higher level of psychological distress. The previous study related to traumatic stress events has reported that those in the general population with traumatic stress experiences were more likely to adopt a negative coping style [9]. Many previous studies have shown that different coping styles, especially negative coping styles, for trauma stress events are also related to subsequent mental illness [7,10,32].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…The population with negative coping style showed higher level of psychological distress. The previous study related to traumatic stress events has reported that those in the general population with traumatic stress experiences were more likely to adopt a negative coping style [9]. Many previous studies have shown that different coping styles, especially negative coping styles, for trauma stress events are also related to subsequent mental illness [7,10,32].…”
Section: Plos Onementioning
confidence: 99%
“…At the same time, as the epidemic continues, general population gradually experience different levels of psychological distress, such as nervousness, fear of infection, anxiety, depression, sleep problems, and inattention [3,4]. Previous studies have reported that some psychological problems often occur during similar epidemic [5,6] or other traumatic stress events, such as natural disasters [7,8], disease [9], or long-term employment in high stress occupations [10][11][12], and may last for a long time [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The reverse pattern was found after mild TBI. Subjective complaints after mild TBI seem to be strongly influenced by mental distress and post‐traumatic stress disorder rather than by injury severity by itself (de Koning et al, ; Scheenen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…[9]. Multiple researchers suggested integrated biopsychosocial approaches for future studies to best explain the outcome of TBI [80][81][82][83]. However, few studies have yet examined identified biopsychosocial factors in a comprehensive model over time to determine the significant underlying factors that contribute to post-TBI fatigue and sleep problems.…”
Section: Discussionmentioning
confidence: 99%